2015
DOI: 10.1089/neu.2014.3684
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Behavioral Outcomes after a Randomized, Clinical Trial of Counselor-Assisted Problem Solving for Adolescents with Complicated Mild-to-Severe Traumatic Brain Injury

Abstract: Family problem-solving therapy (FPST) has been shown to reduce behavior problems after pediatric traumatic brain injury (TBI). It is unclear whether treatment gains are maintained. We sought to evaluate the maintenance of improvements in behavior problems after a Web-based counselor-assisted FPST (CAPS) intervention compared to an Internet resource comparison (IRC) intervention provided to adolescents within the initial year post-TBI. We hypothesized that family socioeconomic status, child educational status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 23 publications
0
49
0
Order By: Relevance
“…One of the CAPS studies reported a significant decrease in problematic behavioural functioning post-intervention, including decreases in internalizing (p < .05), aggressive (p < .05), attention problems (p < .05), ADHD (p < .05), and conduct disorder symptoms (p < .05) (Wade et al, 2014). A decrease in externalizing behaviours was reported consistently at multiple follow up points compared to an internet resource comparison (p < .01; p = .01; p < .01) (Wade, Taylor, et al, 2015). One of the TOPS studies also found a decrease in internalizing behaviours for the intervention group (p = .03, d = .580) (Wade et al, 2008).…”
Section: Effectiveness Of the Interventionsmentioning
confidence: 93%
See 1 more Smart Citation
“…One of the CAPS studies reported a significant decrease in problematic behavioural functioning post-intervention, including decreases in internalizing (p < .05), aggressive (p < .05), attention problems (p < .05), ADHD (p < .05), and conduct disorder symptoms (p < .05) (Wade et al, 2014). A decrease in externalizing behaviours was reported consistently at multiple follow up points compared to an internet resource comparison (p < .01; p = .01; p < .01) (Wade, Taylor, et al, 2015). One of the TOPS studies also found a decrease in internalizing behaviours for the intervention group (p = .03, d = .580) (Wade et al, 2008).…”
Section: Effectiveness Of the Interventionsmentioning
confidence: 93%
“…Nine studies reported statistically significant results regarding treatment effect (Cook, Chapman, Elliott, Evenson, & Vinton, 2014;Kurowski et al, 2013;Wade et al, 2008;Wade et al, 2010;Wade et al, 2011;Wade et al, 2014;Wade, Kurowski et al, 2015;and Wade, Taylor et al, 2015;Babcock et al, 2017). Of these, Cohen's d effect sizes were reported in three (Cook, Chapman, Elliott, Evenson, & Vinton, 2014;Kurowski et al, 2013;and Wade et al, 2008).…”
Section: Effectiveness Of the Interventionsmentioning
confidence: 99%
“…While not a 'novel' study as such, it is also worth noting an additional study by Wade et al, (2015) detected during this update. Extending on the findings of an earlier study included in the original systematic review (CAPS: this research examines the maintenance of treatment effects during the initial 12-months post treatment completion (as well as the moderating effects of family socioeconomic status on treatment response) providing a valuable contribution to the literature.…”
Section: Addendum To Systematic Review (Feb 2017)mentioning
confidence: 94%
“…The programmes deliver parenting support in a manner that overcomes many of the traditional barriers to support, while maintaining high levels of client satisfaction Wade et al, 2012). While research in relation to telehealth parenting interventions that specifically target, and/or include, adaptations to meet the specialised needs of parents and caregivers of children with a disability is even more limited, the evidence that 29 is available provides similar support to the efficacy of such interventions for improving parent skill and adjustment, as well as child behaviour outcomes, Kable et al, 2012;Pickard, Wainer, Bailey, & Ingersoll, 2016;Wade et al, 2015).…”
Section: Assessing Consumer Preference In Telehealth-based Parent-tramentioning
confidence: 99%
See 1 more Smart Citation